2016
DOI: 10.1016/j.materresbull.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SiO2 layer on the plasmon quenched upconversion luminescence emission of core-shell NaYF4:Yb,Er@SiO2@Ag nanocomposites

Abstract: β-NaYF 4 :Yb,Er@SiO 2 @Ag core-shell hybrid nanostructures are prepared and single core-shell hybrid particle is taken to investigate the influence of separation layer on the metal enhanced upconversion luminescence and corresponding mechanism. It is found that the green ( 4 S 3/2 → 4 I 15/2 ) and red ( 4 F 9/2 → 4 I 15/2 ) emissions of Er 3+ increase first and then decrease with the increase of silica shell thickness. The best enhancement is observed at the silica thickness of 12 nm. Time-resolved spectra stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…† However, these previous studies relied exclusively on a spacer of metal, polymer or SiO 2 for attaching the Au nanoparticles by solution processing, which inhibits the plasmonic enhancement of luminescence due to the apparent parasitic absorption by these materials at the thicknesses required for optimum enhancement. 26,27 This limitation is overcome in this work by a third enhancement method using an undoped inert crystal shell. The thickness of inert shells is highly controllable and can be varied, allowing nanometre control by adjusting the concentration and amount of the shell precursor added during the epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%
“…† However, these previous studies relied exclusively on a spacer of metal, polymer or SiO 2 for attaching the Au nanoparticles by solution processing, which inhibits the plasmonic enhancement of luminescence due to the apparent parasitic absorption by these materials at the thicknesses required for optimum enhancement. 26,27 This limitation is overcome in this work by a third enhancement method using an undoped inert crystal shell. The thickness of inert shells is highly controllable and can be varied, allowing nanometre control by adjusting the concentration and amount of the shell precursor added during the epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%
“…11b. The UC emission intensities and the ratio of various emissions are influenced by the doping level, excitation power, preparation temperature [38], impurities, surface ligands, solvent and defects [16]. The peak intensity of 0.5% Yb, 0.25% Er and 1.5% Yb, 0.75% Er are the next intense red emission after 4%Yb, 2%Er concentration and pure.…”
Section: Pl Analysismentioning
confidence: 99%
“…14). It is already reported that the higher concentration of upconversion nanoparticles along with anticancer drug (cisplatin) displays higher toxicity to cancer cells especially on human cervical carcinoma cell line (HeLa cells) and reduced toxicity at lower concentrations of the same cell line than the actual cancer drug [38,39,45]. Xiong et al [46] estimated the cellular viability and have shown the low toxicity to HeLa cell lines until 400 μM concentration.…”
Section: Mtt Assaymentioning
confidence: 99%
“…Up to now, many strategies have been proposed to improve the luminescence property in order to enhance its intensity. These methods include matrix modification, introduction of dopant sensitizer, application of core/shell configuration, and metal enhanced fluorescence effect, etc [8][9][10][11][12]. Local surface plasmon resonance (LSPR) of noble metal nanostructure is considered as the origin of metal enhancement effect and is used to enhance upconversion(UC) luminescence efficiency [8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
“…These methods include matrix modification, introduction of dopant sensitizer, application of core/shell configuration, and metal enhanced fluorescence effect, etc [8][9][10][11][12]. Local surface plasmon resonance (LSPR) of noble metal nanostructure is considered as the origin of metal enhancement effect and is used to enhance upconversion(UC) luminescence efficiency [8][9][10][11][12][13][14]. Excitation field enhancement and emission field enhancement, which is resulted from the local field enhancement, are considered as two essential factors for obtaining metal enhanced fluorescence effect [15][16][17][18][19][20].…”
mentioning
confidence: 99%